REFORMASI PELAYANAN PUBLIK SEBUAH KEHARUSAN (Studi Penelitian pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Timor Tengah Utara) - Botha, Hendrikus Hironimus; Naif, Yohanes Imanuel; Minggu, Pionisius (Journal of Education on Social Science (JESS), 2024)
This paper discusses the importance of a public administration reform in the aspect of public service. Public administration reform related to aspects of public service is a must considering that the better public services provided by the government for the people reflect the government's attention to the needs of the community. Public service reform should be carried out continuously and follow changes and developments in community needs and the existing environmental situation. This paper is intended to explain the implementation of public service reform at the North Central Timor District Population and Civil Registry Service. The research method used is a qualitative method and the theoretical reference is the dimension of public service according to Parasurahman. The novelty of this paper lies in the theory used, namely the author analyzes public services by using all dimensions of public service put forward by Parasurahman to provide a thorough analysis of the object of research. The results of the research findings show that public service reform has been implemented, including through the use of new service buildings, recruitment of Human Resources, implementation of a Centralized Administrative Information System and implementation of the 'personal selling' service mechanism. Based on these findings, there is one service mechanism which is an innovation from the Population and Civil Registry Service, namely the 'personal selling' service which has had a significant impact on the realization of quality public services.